Sistem Pengembangan Pembelajaran Kitab Kuning dalam Meningkatkan Intelektualitas Santri di Yayasan Pondok Pesantren Madinatul ‘Ulum NW Mumbang Desa Montong Gamang: Yellow Book Learning Development System in Improving the Intellectuality of Santri - Syahdan; Abdul Haris Rasyidi; Fatihul Akbar (Pendidikan Al-Gafari, 2026)
Islamic boarding school education is a style of education that is characteristic of the Indonesian nation and its contribution to education in this country is beyond doubt. For decades, even more than a century, Islamic boarding schools have contributed to educating the nation's children. The aim of this research is to determine the development system and implications of learning the yellow book in improving the intellectuality of students at the Madinatul 'Ulum NW Mumbang Islamic Boarding School. To obtain data for this research, the author used qualitative descriptive research using observation, interview and documentation techniques. As a result of the research, it was found that in Islamic boarding schools, yellow book learning is being developed from several aspects, namely: learning methods and developing learning plans. In developing the learning of the Yellow Book, this Islamic boarding school faces various kinds of obstacles as follows: Difficulty understanding Arabic, students having difficulty interpreting the Yellow Book, having difficulty memorizing, and students having no enthusiasm or motivation in learning the Yellow Book.